Voices of the enslaved : love, labor, and longing in French Louisiana - White, Sophie (Omohundro Institute of Early American History and Culture ; University of North Carolina Press, 2019)
"In eighteenth-century New Orleans, the legal testimony of some 150 enslaved women and men--like the testimony of free colonists--was meticulously recorded and preserved. Questioned in criminal trials as defendants, victims, and witnesses about attacks, murders, robberies, and escapes, they answered with stories about themselves, stories that rebutted the premise on which slavery was founded. Focusing on four especially dramatic court cases, Voices of the Enslaved draws us into Louisiana's courtrooms, prisons, courtyards, plantations, bayous, and convents to demonstrate how enslaved people viewed and experienced their worlds. Sophie White offers both a richly textured account of slavery in French Louisiana and a powerful meditation on the limits and possibilities of the archive"--